Empowering users’ privacy through a centralized platform to respond to a pervasive and mobile computing world - Cunha, Carlos R. (2016)
Technologies for contextualization and Recognition of people and situations have made great progresses in the last years. Every time we use the Internet, pass by car in auto ways, enter inside a commercial shopping, even when we go on street, there are in-build space mechanisms capable of getting our personal data – video surveillance, our position through the tracking cell phones position or even when we post a message on some Social Network and we have GPS coordinates associated. Basically we share where we are, what we are doing and with time, we reveal our pattern behaviours. But what we get in return by sharing all this Information? Very few, but it could be a lot. That's the start point of this paper, that review the state of art of contextualization and recognition technologies, discuss is business and social potential and finishes with the presentation of an architecture for supporting a user-centered approach for the definition of a rules-engine capable of translating the users' interests and provide enterprises a source of useful information.